2007
DOI: 10.1103/physreva.75.062120
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible decay of nonlocal entanglement via a reservoir of a single degree of freedom

Abstract: Recently, it has been realized that nonlocal disentanglement may take a finite time as opposite to the asymptotic decay of local coherences. We find in this paper that a sudden irreversible death of entanglement takes place in a two atom optical Stern-Gerlach model. In particular, the one degree non dissipative environment here considered suddenly destroys the initial entanglement of any Bell's states˛φ ±¸s uperposition.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Since the first theoretical demonstration of ESD, further investigations of different systems have been made by various groups [4,5,6,7,8,9,10,11,12,13]. Extending Yu and Eberly's model by considering correlated reservoirs and interactions [5,8,10,12,13], it was shown that entanglement may be created by spontaneous emission (something which has been known for some time [17] in a different context). The ESD has also been predicted for more complicated systems using other entanglement measures [15,16], and an attempt to give a geometric interpretation for the phenomena of ESD has also been made [18].…”
mentioning
confidence: 99%
“…Since the first theoretical demonstration of ESD, further investigations of different systems have been made by various groups [4,5,6,7,8,9,10,11,12,13]. Extending Yu and Eberly's model by considering correlated reservoirs and interactions [5,8,10,12,13], it was shown that entanglement may be created by spontaneous emission (something which has been known for some time [17] in a different context). The ESD has also been predicted for more complicated systems using other entanglement measures [15,16], and an attempt to give a geometric interpretation for the phenomena of ESD has also been made [18].…”
mentioning
confidence: 99%
“…3, it clearly shows that when the detuning increases the entanglement decreases and oscillates fast [36], and it is interesting to note that when the detuning and the atomic motion are all considered, a damping evolution of the entanglement arises. The former is attributed to the fact that on having large dutunings, the atomic system is weakly coupled to the radiation field, and the latter may be referred to a quantum decoherence [37,38,39] when the interaction between the internal and the external atomic dynamics is considered (see Fig.3(b)). Also, it is shown that the atomic motion can lead to a damping in the correlation functions of non classical behaviors between the field and internal atomic variables, which induces the separability of the atom and the field in [38].…”
Section: Entanglement Evolution For the Bipartite Systemmentioning
confidence: 99%
“…Considering the motion of the atoms, the Tavis-Jaynes-Cummings model (TJCM) with two moving atoms has been investigated [15] and the researchers have shown that the ESD and ESB [16] have also been experimentally observed for entangled photon pairs [17] and the atom ensembles [18]. In addition to those, the entanglement of two moving atoms interacting with a single-mode field via a three-photon process is also investigated [19].…”
Section: Introductionmentioning
confidence: 99%